RANCANG BANGUN CONTROLLER BLDC BERBASIS MIKROKONTROLER STM32 BLUE PILL PADA KENDARAAN LISTRIK URBAN AGNIJAYA WEIMANA - Ngadeg A. C., Mas Nyoman; Satya Kumara, I Nyoman; Elba Duta Nugraha, I Putu (Jurnal SPEKTRUM; Vol 9 No 3 (2022): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2022.v09.i03.p7, 2022)
The increase in the consumption of fuel oil causes the depletion of fossil fuel reserves. One alternative energy solution that can be utilized is electrical energy. One of the efforts to overcome the energy crisis can be realized in a creativity in the energy efficient car contest (KMHE). The Weimana Team of Udayana University participated in the urban concept category of electric motor drive under the name Agnijaya Vehicle. One important aspect in order to be able to compete and win the competition is the Motor Controller. In this paper, the results of the research are presented on a design of a Brushless DC Motor Controller based on the STM32 Blue Pill microcontroller and used to rotate the BLDC motor on the Agnijaya Weimana Urban Electric Vehicle. The specifications of the BLDC controller design are made to have a power dissipation inverter with a power of 1980 Watt connected to an 800 Watt sensored BLDC motor. The STM32 Blue Pill microcontroller-based Brushless DC Motor Controller has been successfully designed and manufactured and produces a sinusoidal output waveform containing switching noise when connected to a no-load BLDC motor. The performance to drive Agnijaya Wimana's Urban Electric Vehicle is capable of implementing a PWM duty cycle of up to 100% with an average current achievement of 24,775 Ampere, an average voltage drop of up to 48,485 VDC, an average power rating of up to 1200,5 Watt and a BLDC motor speed up to 419,5 RPM.